PERBANDINGAN PENGGUNAAN ANTIPSIKOTIK ATIPIKAL TUNGGAL DAN KOMBINASI TERHADAP KADAR KOLESTEROL PADA PASIEN SKIZOFRENIA - TARISA ANANDASMARA; ISRA THRISTY (LP2MTBM MAKARIOZ, 2023)
Schizophrenia is a psychiatric disease that causes the most psychological and social problems. This disease requires antipsychotic therapy for a long time, so it is very possible in the treatment process to find problems in the use of antipsychotics, one of which is an increase in total cholesterol levels. This study aims to determine differences in total cholesterol levels in schizophrenia patients who use single and combination atypical antipsychotics at RSU. Madani Medan. The research design used is descriptive analytic with a cross-sectional study. The sample used in this study amounted to 30 samples. Samples were taken using a single atypical antipsychotic as many as 15 people and 15 people using a combination atypical antipsychotic. Then the sample is checked at UPT. The Regional Health Laboratory (KESDA) uses the CHOD-PAP (Cholesterol Oxidase-Peroxidase Aminoantypirin) method with a photometer. Then the data is processed with the SPSS program. From 30 samples used, it was found that 15 samples using a combination atypical antipsychotic experienced an increase in cholesterol levels (50%) and 15 samples using a single atypical antipsychotic did not experience an increase in cholesterol levels (50%). Based on the results of this study, it can be concluded that there is difference in cholesterol levels in the use of single and combined atypical antipsychotics in schizophrenic patients as evidenced the p-value obtained, which is 0.000 (p <0.05).